ANALISIS PELAKSANAAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DI SMA: LITERATUR REVIEW DALAM KAJIAN EKONOMI KERAKYATAN - Indah Wati; Kiromim Baroroh; Paijan Rambe; Ristiliana Ristiliana (Eklektik : Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study aims to evaluate the implementation of the Pancasila Student Profile Strengthening Project (P5) in high schools, focusing on its role in enhancing Pancasila values, developing student character, and its effects on students' social-emotional well-being. The research utilizes a literature review of six Scopus-indexed articles that explore different aspects of P5, including character education, technology integration, and religious moderation. The results indicate that P5 has effectively improved students' understanding of national values, fostered active democratic participation, and promoted the development of 21st-century skills through the integration of artificial intelligence (AI) in STEM education. Furthermore, the project has reinforced religious moderation and contributed to creating a more inclusive school environment. It is recommended to strengthen the leadership of school principals, improve teacher training, and establish community partnerships to enhance the overall effectiveness of the project in meeting national educational objectives.